Amino acid derivatives as transdermal permeation enhancers - Janůšová, Barbora; Skolová, Barbora; Tükörová, Katarína; Wojnarová, Lea; Simůnek, Tomáš; Mladěnka, Přemysl; Filipský, Tomáš; Ríha, Michal; Roh, Jaroslav; Palát, Karel; Hrabálek, Alexandr; Vávrová, Kateřina (Journal of controlled release, 2013)
Transdermal permeation enhancers are compounds that temporarily decrease skin barrier properties to promote drug flux. In this study, we investigated enhancers with amino acids (proline, sarcosine, alanine, β-alanine, and glycine) attached to hydrophobic chain(s) via a biodegradable ester link. The double-chain lipid-like substances displayed no enhancing effect, whereas single-chain substances significantly increased skin permeability. The proline derivative l-Pro2 reached enhancement ratios of up to 40 at 1% concentration, which is higher than that of the well-established and standard enhancers Azone, DDAIP, DDAK, and Transkarbam 12. No stereoselectivity was observed. l-Pro2 acted synergistically with propylene glycol. Infrared studies revealed that l-Pro2 forms a separate liquid ordered phase in the stratum corneum lipids and has no significant effect on proteins. l-Pro2 action was at least partially reversible as measured by skin electrical impedance. Toxicity in keratinocyte (HaCaT) and fibroblast (3T3) cell lines showed IC(50) values ranging from tens to hundreds of μM, which is comparable with standard enhancers. Furthermore, l-Pro2 was rapidly decomposed in plasma. In vivo transdermal absorption studies in rats confirmed the enhancing activity of l-Pro2 and suggested its negligible skin toxicity and minimal effect on transepidermal water loss. These properties make l-Pro2 a promising candidate for potential clinical use.
Keywords: Proline; Skin Absorption; kožní absorpce; Drug Stability; kůže; Animals; Humans; Mice; aminokyseliny; prolin; Skin; keratinocyty; krevní plazma; krysa rodu Rattus; Amino Acids; Rats; Swine; Permeability; Cell Line; Administration, Cutaneous; zvířata; prasata; 3T3 Cells; Keratinocytes; aplikace kožní; stabilita léku; Plasma; lidé; permeabilita; buněčné linie; buňky 3T3; myši